(untitled) (Revista de Estudos da Linguagem, 2024)
Taboo words are emotional words which, in psycho and neurolinguistic studies, present higher attentional capture, are more memorable and complex to process. Such phenomena are connected to dimensions such as arousal and valence, which reflect social, psychological and neurological aspects. The present study, the first of its kind in Brazilian Portuguese, aims to collect normative data in order to characterize what distinguish the processing of taboo words from other emotional words. The study crosses over to sociolinguistics by mapping linguistic attitudes towards taboo words, which are salient stylistic elements, subject to negative judgement, and strongly engage the sociolinguistic monitor. We aim to examine how certain aspects that may underlie beliefs and linguistic attitudes, such as gender, religiosity, habit of engaging in swearing, family tolerance and likelihood to take offense, modulate taboo word perception. Answers given by 164 university students from Rio de Janeiro to an explicit questionnaire about swear words were compared to less explicit judgements on 200 words in order to examine: (i) whether frequency, familiarity, valence, offensiveness, tabooness and arousal set taboo words apart from other categories (positive, negative and neutral words); (ii) the influence of participants’ sociocultural profile on such judgements, reflecting sociolinguistic monitoring. We observed that taboo words fall into a distinct category, mainly due to high social tabooness and offensiveness ratings, but also due to low familiarity and negative valence. These results confirm more negative linguistic attitudes regarding taboo words influenced by religiosity, family environment and gender, pertinent aspects to the understanding of these speakers’ linguistic identity.